Designing Effective Speech-Language Interventions for Children in the Public Schools: Leverage the Spacing Effect. (March 2016) - Justice, Laura M.; Logan, Jessica; Schmitt, Mary Beth; Jiang, Hui
In the U.S. public school system, more than 6 million children receive special education services, including many children with speech and language impairments. Speech-language pathologists (SLPs) design and implement effective interventions—including how much intervention children receive—to circumvent the negative effects of speech-language impairments on educational outcomes. Existing policy and position statements suggest that increasing the number of sessions (frequency) and amount of intervention (dose) would improve children's outcomes, assuming that greater treatment intensity is associated with better treatment outcomes. However, current empirical evidence, coupled with cognitive theory, suggests that more treatment may not relate to improved outcomes. The present article draws on current empirical studies and established cognitive theories of spacing effects (learning distributed over time) to propose a systematic way for SLPs to plan and implement an effective intensity of intervention for children with speech and language impairments.